Humanização da arquitetura hospitalar : diretrizes projetuais para espaços criativos de internação pediátrica - Sebben, Victória Andreis (Universidade do Vale do Rio dos Sinos, 2020)
Contemporary health establishments point to a new perspective based on a more humanized relationship with users, which involves the valorization of all parties while conceiving the architectural building. In that sense, this search will approach the thematic of humanization of hospital architecture in different applications around the world, with particular attention to creative spaces in the pediatric inpatient unit. Aiming to develop project elements, as a way of promoting a humanized healthcare environment in this specific unit, a bibliographic review was conducted, summed with a systematic literature review, subsequent application of interview to a focused group, and a project exercise with architects, formulating the research method of this study. The results allow the present study to propose improvements in the respective already existing spaces, help to design and create new spaces, and even to serve as a basis to replicate the referred concept in any other units in hospital establishments.
Keywords: Arquitetura hospitalar; Humanização; Espaços criativos; Design na saúde; Design para o bem-estar; Pediatria; Crianças; Hospital architecture; Humanization; Healthcare design; Design for wellbeing; Pediatrics; Children; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo